Centre of interests of that person: comments to the CJUE judgement of 17 octuber 2017, Bolagsupplysningen Oü, Ingrid Ilsjan y Svensk Handel ab, c-194/16 - Merchán Murillo, Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The CJUE judgement of 17 Octuber 2017, Bolagsupplysningen OÜ, Ingrid Ilsjan y Svensk Handel Ab, C-194/16, refers to a new interpretation regarding Art. 7,2 of Regulation 1215/2012, in relation to non-contractual obligations, and determines that legal persons can file a claim for violation of their personality rights before the Member State’s courts where they locate their center of interests. This center of interest will be determined by the place where the essential part of its economic activity is exercised.
Keywords: Regulation 1215/2012; non contractual obligations; rights relating to personality; center of interest